A microabrasion wear study of nitrided α-Ti and β-TiNb PVD metallic thin films, pre-deposited onto titanium alloy substrates - YUMUŞAK, GÖRKEM (My University, 2022)
© 2022 Elsevier B.V.In this paper, we study the structure, mechanical properties and abrasion resistance of two triode-plasma nitrided (TPN) titanium alloys, pre-coated with metallic α-Ti or β-TiNb layers deposited by physical vapour deposition (PVD). The chosen alloys were Ti-6Al-4V and Ti-4Al-10V-22Mo, which are predominantly alpha- and beta-phased, respectively – each presenting different challenges, in terms of their nitriding response. Although duplex nitriding + PVD coating is now quite widely employed on steels (and increasingly on titanium alloys) to improve load-bearing capacity and wear resistance, the use of PVD coatings prior to diffusion treatment to control surface roughness – and, in the case of Ti-alloys particularly, to optimise their ‘challenging’ diffusion kinetics has received little or no attention so far. The TPN process enables diffusion treatments to be carried out at 700 °C – which is lower than the beta-transus temperature of Ti (and of most Ti alloys). Optical microscopy, scanning electron microscopy, atomic force microscopy, X-ray diffraction, nanoindentation, and surface profilometry were used to characterize the nitrided and coated/nitrided samples. It was found that the nitrogen concentration and surface hardness for all samples was significantly increased, and that the surface roughness values significantly increased for uncoated Ti alloy substrates after TPN treatment – due to intense, grain orientation-dependent plasma etching effects. However, our novel approach of PVD pre-deposition of a nanostructured metallic coating prior to nitriding reduces surface roughening effects quite dramatically. The micro-abrasion resistance of Ti- and TiNb-coated Ti-6Al-4V substrates was significantly enhanced after nitriding treatment; on the other hand, similar improvements were not found for the metastable-beta Ti-4Al-10V-22Mo substrates – due to the different nitriding behaviour of the pre-deposited PVD surface layers. The \"sputter removal\" rates for the metallic coatings were high, but all coatings survived in part until the end of the nitriding process.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; KİMYA, FİZİKSEL; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; PHYSICS; MATERIALS SCIENCE, MULTIDISCIPLINARY; CHEMISTRY, PHYSICAL; PHYSICS, CONDENSED MATTER; Genel Kimya; Fizik Bilimleri; Yoğun Madde Fiziği; Yüzeyler ve Arayüzler; Yüzeyler, Kaplamalar ve Filmler; Malzeme Kimyası; General Chemistry; Physical Sciences; Condensed Matter Physics; Surfaces and Interfaces; Surfaces, Coatings and Films; Materials Chemistry; Titanium-niobium coatings; PVD; Triode plasma nitriding; Micro-abrasion test; TRIODE PLASMA-DIFFUSION; SURFACE; TI-6AL-4V; NITROGEN; BEHAVIOR; KINETICS; Titanium-niobium coatings; PVD; Triode plasma nitriding; Micro-abrasion test